Waste-to-value: Optimizing methanotrophic culture enrichment from activated sludge using a synthetic wastewater effluent - Lisa Stephanie H. Dizon; Robert S. Bertrand; William E. Holmes; Rafael A. Hernandez; Andrei Y. Chistoserdov; Wayne W. Sharp; Dhan Lord B. Fortela; Mark E. Zappi; Emmanuel D. Revellame (Journal of Environmental Chemical Engineering, 2026)

Downregulation of Fidgetin-Like 2 Increases Microglial Function: The Relationship Between Microtubules, Morphology, and Activity - Austin N. Smith; Alison Gregor; Lisa Baker; David J. Sharp; Kimberly R. Byrnes (Molecular Neurobiology, 2025)
The microtubule cytoskeleton regulates microglial morphology, motility, and effector functions. The microtubule-severing enzyme, fidgetin-like 2 (FL2), negatively regulates cell motility and nerve regeneration, making it a promising therapeutic target for central nervous system injury. Microglia perform important functions in response to inflammation and injury, but how FL2 affects microglia is unclear. In this study, we investigated the role of FL2 in microglial morphology and injury responses in vitro. We first determined that the pro-inflammatory stimulus, lipopolysaccharide (LPS), induced a dose- and time-dependent reduction in FL2 expression associated with reduced microglial ramification. We then administered nanoparticle-encapuslated FL2 siRNA to knockdown FL2 and assess microglial functions compared to negative control siRNA and vehicle controls. Time-lapse live-cell microscopy showed that FL2 knockdown increased the velocity of microglial motility. After incubation with fluorescently labeled IgG-opsonized beads, FL2 knockdown increased phagocytosis. Microglia were exposed to low-dose LPS after nanoparticle treatment to model injury-induced cytokine secretion. FL2 knockdown enhanced LPS-induced cytokine secretion of IL-1α, IL-1β, and TNFα. These results identify FL2 as a regulator of microglial morphology and suggest that FL2 can be targeted to increase or accelerate microglial injury responses. Graphical Abstract

Moche chronology of ancient Peru: Bayesian assessment of radiocarbon dates and ceramic styles from north to south - Michele L. Koons; Branden Cesare Rizzuto; Lisa Trever; Alicia Boswell; Augusto Bazán Pérez; Luis A. Muro Ynoñán; Gabriel Prieto; Carlos Rengifo; Kayeleigh Sharp; Edward Swenson; Hugo Ikehara-Tsukayama; Jessica Ortiz Zevallos; et al. (Quaternary International, 2024)

Use of multiple endpoints to assess the impact of captivity on gut flora diversity in Long Island Sound Fundulus heteroclitus - Joseph P. Battaglia; Christian M. Kearney; Kirsten Guerette; Jordan Corbishley; Emily Sanchez; Brennah Kent; Hanna Storie; Emma Sharp; Shane Martin; Matthew Saberito; Jonathan D. Blake; Richard S. Feinn; et al. (Environmental Biology of Fishes, 2022)

Self-reported health and survival in older patients diagnosed with multiple myeloma - Nadia A. Nabulsi; Ali Alobaidi; Brian Talon; Alemseged A. Asfaw; Jifang Zhou; Lisa K. Sharp; Karen Sweiss; Pritesh R. Patel; Naomi Y. Ko; Brian C.-H. Chiu; Gregory S. Calip (Cancer Causes & Control, 2020)

Unoccupied aerial system assessment of entanglement in Northwest Atlantic gray seals ( Halichoerus grypus ) - Maria Clara Iruzun Martins; Lisa Sette; Elizabeth Josephson; Andrea Bogomolni; Kathryn Rose; Sarah M. Sharp; Misty Niemeyer; Michael Moore (Marine Mammal Science, 2019)

Closing the global ozone yield gap: Quantification and cobenefits for multistress tolerance - Gina Mills; Katrina Sharps; David Simpson; Håkan Pleijel; Michael Frei; Kent Burkey; Lisa Emberson; Johan Uddling; Malin Broberg; Zhaozhong Feng; Kazuhiko Kobayashi; Madhoolika Agrawal (Global Change Biology, 2018)
Increasing both crop productivity and the tolerance of crops to abiotic and biotic stresses is a major challenge for global food security in our rapidly changing climate. For the first time, we show how the spatial variation and severity of tropospheric ozone effects on yield compare with effects of other stresses on a global scale, and discuss mitigating actions against the negative effects of ozone. We show that the sensitivity to ozone declines in the order soybean > wheat > maize > rice, with genotypic variation in response being most pronounced for soybean and rice. Based on stomatal uptake, we estimate that ozone (mean of 2010–2012) reduces global yield annually by 12.4%, 7.1%, 4.4% and 6.1% for soybean, wheat, rice and maize, respectively (the “ozone yield gaps”), adding up to 227 Tg of lost yield. Our modelling shows that the highest ozone‐induced production losses for soybean are in North and South America whilst for wheat they are in India and China, for rice in parts of India, Bangladesh, China and Indonesia, and for maize in China and the United States. Crucially, we also show that the same areas are often also at risk of high losses from pests and diseases, heat stress and to a lesser extent aridity and nutrient stress. In a solution‐focussed analysis of these results, we provide a crop ideotype with tolerance of multiple stresses (including ozone) and describe how ozone effects could be included in crop breeding programmes. We also discuss altered crop management approaches that could be applied to reduce ozone impacts in the shorter term. Given the severity of ozone effects on staple food crops in areas of the world that are also challenged by other stresses, we recommend increased attention to the benefits that could be gained from addressing the ozone yield gap.

Ozone pollution will compromise efforts to increase global wheat production - Gina Mills; Katrina Sharps; David Simpson; Håkan Pleijel; Malin Broberg; Johan Uddling; Fernando Jaramillo; William J Davies; Frank Dentener; Maurits Van den Berg; Madhoolika Agrawal; Shahibhushan B. Agrawal; et al. (Global Change Biology, 2018)
Introduction of high‐performing crop cultivars and crop/soil water management practices that increase the stomatal uptake of carbon dioxide and photosynthesis will be instrumental in realizing the United Nations Sustainable Development Goal ( SDG ) of achieving food security. To date, however, global assessments of how to increase crop yield have failed to consider the negative effects of tropospheric ozone, a gaseous pollutant that enters the leaf stomatal pores of plants along with carbon dioxide, and is increasing in concentration globally, particularly in rapidly developing countries. Earlier studies have simply estimated that the largest effects are in the areas with the highest ozone concentrations. Using a modelling method that accounts for the effects of soil moisture deficit and meteorological factors on the stomatal uptake of ozone, we show for the first time that ozone impacts on wheat yield are particularly large in humid rain‐fed and irrigated areas of major wheat‐producing countries (e.g. United States, France, India, China and Russia). Averaged over 2010–2012, we estimate that ozone reduces wheat yields by a mean 9.9% in the northern hemisphere and 6.2% in the southern hemisphere, corresponding to some 85 Tg (million tonnes) of lost grain. Total production losses in developing countries receiving Official Development Assistance are 50% higher than those in developed countries, potentially reducing the possibility of achieving UN SDG 2. Crucially, our analysis shows that ozone could reduce the potential yield benefits of increasing irrigation usage in response to climate change because added irrigation increases the uptake and subsequent negative effects of the pollutant. We show that mitigation of air pollution in a changing climate could play a vital role in achieving the above‐mentioned UN SDG , while also contributing to other SDG s related to human health and well‐being, ecosystems and climate change.

Influence of age, sex, and aerobic capacity on forearm and skin blood flow and vascular conductance - Gary J. Hodges; Lisa Sharp; Richard E. Clements; David F. Goldspink; Keith P. George; Nigel T. Cable (European Journal of Applied Physiology, 2010)

The effect of 48 weeks of aerobic exercise training on cutaneous vasodilator function in post-menopausal females - Gary J. Hodges; Lisa Sharp; Claire Stephenson; Ashish Y. Patwala; Keith P. George; David F. Goldspink; N. Tim Cable (European Journal of Applied Physiology, 2010)